THE INFLUENCE OF SPATIAL, ECONOMIC AND SOCIAL TRANSFORMATION IN THE DEVELOPMENT OF A LANDSCAPE VALORISATION STRATEGY - Ivanov, Metodi (International Multidisciplinary Scientific GeoConference SGEM, 2024)
The aim of this paper is to assess the impact of spatial, economic and social transformation and their influence on the development of a landscape valorization strategy, in terms of the possibilities for implementing structural changes in the territory of a country, through which structural changes to support the introduction of new technologies and innovations, resulting in a change in the sectoral structure of a country's economy. On the other hand, by assessing the impact of social transformation, an explanation will be sought for a number of processes related to the motivation to upskill the workforce in different regions, and possible ways of stimulating them will be sought by creating opportunities to improve the existing business environment in lagging regions in developing countries. An assessment of the role of spatial transformation is necessary in view of creating the conditions to stimulate investment in lagging regions, and to achieve sustainable development through a balanced use of available resources. On the other hand, the need to develop a strategy for the valorisation of the landscape should be highlighted in the light of an assessment of spatial, economic and social transformation, in the context of the objectives set by a number of countries to achieve the transition to a low-carbon and digitalised economy. This process, on the other hand, implies considerable efforts to increase the digital skills of the population, which will have an impact on the development of personal and collective incentives for the development and application of innovation in the socio-economic life of the population in the regions. On the other hand, the need to develop a valorisation strategy for the landscape is underlined by the search for opportunities to increase investment in green technologies in productive activities.